Evaluating Carcass Traits of Sheep and Benchmarking of Slaughter Premises in Coastal Districts of Andhra Pradesh : 10.5958/2581-6616.2020.00005.5 - Mallika, E. Naga; Venu, T.; Rao, B. Eswara; Rao, T. Srinivasa; Rao, V. Giridhara (Journal of Meat Science, 2021)
A survey was conducted in coastal districts of Andhra Pradesh to estimate the post-harvest economics of sheep slaughtered in munic ipal slaughter houses and rural meat stalls and to benchmark the slaughter premises of sheep. This survey revealed a higher degree of unauthorised slaughter as a result of shutting down of some of the existing slaughter houses by Supreme Court order because of lack of effluent treatment plants. The other findings of the survey revealed lower levels of knowledge of butchers on SOPs and personal hygiene. The recycling of the waste was not carried out at satisfactory level and effluent treatment plants were not established. In sheep meat market, direct involvement of the farmer was very low and middlemen were playing a major role except in case of rural meat stalls, where slaughter unauthorised was prevailing. The rate of slaughter was higher on weekends when compared to the other days. Post mortem examination was done only in municipal slaughter houses, and Halal method was used for slaughter of sheep irrespective of place of slaughter. But the rate of slaughter and demand were high in street and rural meat stalls. The supply of water and electricity was good. A dressing percentage of 47.85 and 49.61 per cent in sheep along with a sale price of Rs. 570 and 600 per kg for mutton were recorded in municipal slaughter houses and rural meat stalls respectively. Utilization of by-products was almost 100 per cent and survey strongly revealed the dependency of profitability of post-harvest economics of sheep slaughter on by-products utilization. On an average a profit of Rs. 3218 was obtained per animal out of which Rs. 2623 was from by-products which indicates a profit share of 82 per cent is from by-products.